Toplotne razmere v kalcinacijski komori za pečenje anod - Zupanič, Franc (Kovine zlitine tehnologije, 1999)
During continuous monitoring of the primary aluminium production in Talum it was found out that the quality of prebaked anodes is non-uniform. As a result, high nett consumption of anodes in the electrolysis B and often horizontal cracking of anodes for electrolysis C have occured. These problems may arise from different sources, one of these are non-uniform conditions in the anode baking furnace. In this investigation we determined the temperature distribution inside one chamber of the anode baking furnace. Results indicate that the temperature distribution is non-uniform. Therefore, we conclude that non-uniform conditions inside the chamber significantly contribute to variable properties of prebaked anodes.
Keywords: aluminij; aluminum; pribobivanje; anode; kalcinacija; porazdelitev temperature